2015
DOI: 10.1111/jwas.12214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Acute Toxicity of Nitrite to Meagre, Argyrosomus regius (Asso, 1801)

Abstract: Meagre, Argyrosomus regius, is a candidate marine fish species for aquaculture diversification, presenting a high economic value in the Mediterranean. Tolerance of juvenile meagre to nitrite (NO 2 -N) was determined relating to temperature. Fish (3.2 ± 0.6 g and 5.4 ± 0.9 cm) were exposed to different NO 2 -N concentrations in a series of acute toxicity tests by the static renewal method at three temperatures (18, 22, and 26 C) at a pH of 8.0. Low temperature clearly increased tolerance to NO 2 -N (P < 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Higher mortality in fishes exposed to chlorpyrifos and endosulfan by increasing in the temperature [25] and also higher mortality observed by increasing in the temperature when Salmo gairdneri exposed to mercury [15], Argyrosomus regius exposed to NO 3 [26] and also Oncorhynchus mykiss and bluegills exposed to roundup [27].…”
Section: Discussionmentioning
confidence: 99%
“…Higher mortality in fishes exposed to chlorpyrifos and endosulfan by increasing in the temperature [25] and also higher mortality observed by increasing in the temperature when Salmo gairdneri exposed to mercury [15], Argyrosomus regius exposed to NO 3 [26] and also Oncorhynchus mykiss and bluegills exposed to roundup [27].…”
Section: Discussionmentioning
confidence: 99%
“…According to Kir et al (2015a), Kir et al (2015b) were increased with exposure to ammonia with a linear relation to exposure time and increasing temperature. It was suggested that safe levels of NO 2 À and NH 3 for juvenile meagre should be adjusted according to the water temperature: 17.7 mg/L NO 2 À and 0.10 mg/ L NH 3 at 18°C, 13.9 mg/L NO 2 À and 0.07 mg/L NH 3 at 22°C and 4.9 mg/L NO 2 À and 0.04 mg/L NH 3 at 26°C (Kir et al 2015a(Kir et al , 2015b.…”
Section: Environmentalmentioning
confidence: 98%
“…According to Kir et al. (), Kir et al. () meagre showed higher sensitivity to acute toxicity caused by nitrite (NO 2 − ) and ammonia (NH 3 ) than other marine fish produced in the Mediterranean.…”
Section: Noninfectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Οι πληροφορίες σχετικά με τις σκελετικές ανωμαλίες που μπορεί να προκύψουν κατά τη διάρκεια της ανάπτυξης των εκτρεφόμενων κρανιών είναι ελάχιστες, με κάποια δεδομένα τα οποία αναφέρουν λίγα άτομα με συγχώνευση, παραμόρφωση και καμπυλότητα σπονδύλων του αξονικού σκελετού, μεταβολές στις νευρικές άκανθες και στις ακτίνες, και μικρά ελαττώματα στον σκελετό των πτερυγίων (Soares et al 2018), Όσον αφορά στην επίδραση περιβαλλοντικών παραγόντων στην υγεία του κρανιού, πειραματικές μελέτες απέδειξαν πως ο κρανιός είναι πιο ευαίσθητος σε σχέση με άλλα καλλιεργούμενα είδη (τσιπούρα, λαβράκι) τόσο στην αμμωνία, όσο και στα νιτρώδη ιόντα, ενώ βρέθηκε πως η τοξικότητα αυτών επάγεται με την αύξηση της θερμοκρασίας (Kir et al 2016(Kir et al , 2015.…”
Section: Mycobacterium Marinumunclassified